PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BEI - Mochammad Karim Amrulloh; Dwi Ermayanti Susilo (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2022)
This study aims to analyze the effect of company growth and structure on profitability in state-owned banks listed on the Indonesia Stock Exchange. The research uses quantitative research methods which are carried out through data collection with secondary data, namely the Financial Statements of State-Owned Banks Listed on the Indonesia Stock Exchange for the period 2012-2021. The sample in this study is in the form of balance sheets and profit/loss reports for state-owned banks listed on the Indonesia Stock Exchange for the period 2012-2021, data analysis using multiple linear regression statistical methods and hypothesis testing. The results show that 1) There is a value of the influence of company growth on profitability in BUMN Banking Listed on the Indonesia Stock Exchange with t of 2.765 with t table of 2.02 (t count > t table), the significance value obtained is 0.016 < 0.05 2 ) There is no effect of capital structure on profitability in BUMN banking listed on the Indonesia Stock Exchange, with a t value of 17.344 with a t table of 2.02 (t count < t table), the significance value obtained is 0.000 < 0.05